Estudo teórico da interação de Ácidos Mono e Dicarboxílico com a base Esmeraldina - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Polymers are formed macromolecules formed by smaller molecules or meros. Polyaniline is a conductive polymer when doped with organic and inorganic acids. Thus, through theoretical studies, it was possible to analyze the formation of Emeraldine Salt through Emeraldine Base when doped with mono and dicarboxylic organic acids. Therefore these results were obtained when when the Esmeraldine Base was doped with mono and dicarboxylic acids in aqueous medium by means of quantum mechanics methods MP6 with the the base function 6-311G.
Theoretical study of Acid interaction Mono and Dicarboxylic with Emeraldine base
Keywords: Base Esmeraldina; Sal Esmeraldina; Polianilina; Ácidos; Protonação; Emerald Base; Emerald Salt; Polyaniline; Acids; Protonation; CIENCIAS EXATAS E DA TERRA::QUIMICA